Combined interprofessional education and system intervention to improve screening older adults for dementia and falls. Issue 1 (2nd January 2023) - Litzelman, Debra K.; Butler, Dawn E.; Iloabuchi, Tochukwu; Frank, Kathryn I.; Bo, Na; Tong, Yan; Garrison, Emilie; Roth, Sarah; Vannerson, Julie
ABSTRACT: The objective of this study was to increase screening for falls and dementia by improving interprofessional (IP) providers' and staffs' knowledge and attitudes toward the care of older patients and team-based care. An intervention, including education about screening and an electronic health record (EHR) flowsheet, was rolled-out across eight Federally Qualified Health Centers (FQHC). Participants were 262 IP health providers who served 6670 patients ≥ age 65 > age 65 . An EHR flowsheet with two-item screeners for falls and dementia triggered automatically for patients ≥ age 65. Documentation of screening for falls and dementia was abstracted from the EHR for the year prior to and the year after the interventions began. Baseline screening rates for falls and dementia were flat; from the start of education intervention until EHR live date, screening rates increased significantly; after EHR live date, the screening rates continued increasing significantly. A combined education-system intervention can improve screening for falls and dementia in FQHC.